EVALUASI KLINIS DARI TERAPI LESI STERILISASI DAN PERBAIKAN JARINGAN (LSTR) 3MIX-MP - Reni A. Reni; Tri L. Tri; Etty W. Etty; Harry B. S. Harry; Cheryl A. Cheryl; Sri P. Sri; Floriana S. Floriana; Hoshino E. Hoshino (Faculty of Dentistry, Universitas Indonesia, 2015)
A combination of 3 antibacterial drugs (3Mix), ciprofloxacine, metronidazole an minocycline has not been proved to be effective on all kinds of bacteria in oral lesions, carious lesions, after elimination of causative bacteria, can be repaired by host's healing abilities. A total of 285 cases of 110 caries and 175 endodontic cases, consisted of 296 permanent and 16 primary teeth, were treated by 3Mix, further mixed with propylene glycol (P) and Macrogol (M). Clinical symptoms, even those revealing endodontic disorder, such as percussion pains (63 caes), pains on bite (61 cases), abscess (13 cases) and fistulae (11 cases) were eliminated by one-time application of 3Mix-MP therapy in all cases except for 8 cases which need more than 2 times, easily and quickly in all cases. The results demonstrate that 3Mic-MP therapy would be of great use in dental treatment in Indonesia. Long-term evaluation is in progress.